Environmental impact of ISO 14001 certification in promoting Sustainable development: The moderating role of innovation and structural change in BRICS and MINT, and G7 economies - Elvis K. Ofori; Simplice Asongu; Ernest Baba Ali; Bright Akwasi Gyamfi; Isaac Ahakwa (African Governance and Development Institute (AGDI), 2024)
Since the industrial era, the selection of energy sources to facilitate economic advancement has been criticized because of the resulting ecological calamity. This has prompted the introduction of radical approaches such as ISO 14001, which tackles the drivers of pollution. Therefore, this study analyses the ISO 14001 - environment nexus from three distinct points of view BRICS, MINT, and G7 countries from 1999-2020. Also, our work fills an extant gap in assessing structural change and innovation's role in augmenting the relationship. The Driscoll and Kraay (DK) estimator is employed as an analytical tool for cross-sectional dependence and slope homogeneity, while the fixed effects approach provides sufficient robustness checks on the findings. While some outcomes vary per bloc, others are relatively similar across the three (3) blocs. That is: (1) ISO 14001 shows an abatement portfolio for only the G7 bloc, and the Full sample. (2) Structural change showed potential for abating carbon emissions in all blocs. (3) Technology led to an increase in Pollution in all blocs except for the MINT economy. (4) ICT in the form of mobile phones also help reduce carbon emissions in all three blocs except for their composite. (5) Renewable energy helps reduce carbon emission in all blocs except for G7. ISO 14001 shows the potential to encourage green growth. As a result, policymakers should work to enhance ISO 14001 certification, which might serve as a management tool to promote sustainable development.
Keywords: 330; ISO 14001; Sustainable development; Structural change; Technology; BRICSMINT; G7